Impact of soil compaction degree modulated by initial water content on maize root phenotype and hydraulic properties - Fu, Yuanyuan; Si, Zhuanyun; Ma, Shoutian; Cheng, Yahui; Liu, Zhandong; Gao, Yang (Frontiers in Plant Science, 2026)
IntroductionMechanical compaction limits crop production potential by disrupting soil structure and inhibiting root growth. To achieve precise and sustainable agricultural management, it is necessary to clarify the response patterns of compaction effects on root development and water conduction under different initial moisture contents.MethodsIn this study, Zheng58 and Chang7-2, were subjected to a compaction force of 350 kPa under two initial moisture levels of 40% and 80% of field capacity (FC). The effects of compaction on root morphology, aerenchyma formation, and root hydraulic conductivity were investigated. Results and discussionThe results show that soil compaction significantly affected root morphology, aerenchyma formation, and hydraulic conductivity of maize seedlings, and these effects depended on the initial soil moisture at the time of compaction. Regarding root morphology, compaction increased root diameter in both, maize cultivars by 11.6%-43.2%, but at 80% FC, root length was significantly reduced by approximately 72%, and the proportion of fine roots decreased by 5.0%-6.3%. For aerenchyma area, compaction substantially promoted the expansion of aerenchyma area the root-shoot junction, with the most pronounced increase observed at 40% FC. The effect of soil compaction on theoretical root hydraulic conductivity at both the 2.5cm root apex and the root-shoot junction was strongly influenced by the soil moisture at the time of compaction: under 40% FC, theoretical root hydraulic conductivity significantly increased, whereas at 80% FC, it decreased by 67.1%-78.9% at the apex and 40.2%-41.4% at the root-shoot junction. These results indicate that high soil moisture exacerbates the inhibitory effect of compaction on root hydraulic function, highlighting the importance of managing soil moisture to mitigate compaction stress.